New records of polyporoid fungi on Abies religiosa wood in Mexico - Raymundo, Tania; Palacios-Pacheco, Mauricio R.; Bautista-Hernández, Silvia; Valenzuela, Ricardo (Instituto de Ecología, A.C., 2015)
Meruliporia incrassata, Physisporinus rivulosus, Pycnoporellus alboluteus and Skeletocutis alutacea are recorded for the first time for Mexico, and the known distribution of Fibroporia vaillantii is extended to the state of Mexico. These species cause white or brown rot on wood of Abies religiosa. The specimens were collected in the states of Mexico and Tlaxcala, and are deposited in the ENCB and TLXM herbaria.